Impact of vision problems on children’s daily activities: Insights from a focus group discussion [version 2; peer review: 2 approved, 1 not approved] - Rekha Hansraj; Tshubelela Sello Simon Magakwe; Zamadonda Nokuthula Xulu-Kasaba (F1000Research)
Background/Purpose There are approximately 18.94 million visually impaired children worldwide, with 90% of them living in low-middle income countries. Research shows that visual impairment (VI) has a significant impact on the quality of life (QoL) of those affected. Therefore, it is essential to investigate how VI affects the daily activities of these children to develop management strategies that can help minimize its impact on their QoL. Therefore, qualitative research design was utilized to explore the perceived impact of VI on the daily activities of children living with VI. Methods Using a qualitative approach, purposive sampling was used to identify information-rich participants to partake in focus group discussions (FGDs) and address the aim of the study adequately. Identified data sources were divided into two groups: one with ‘experts’ who worked with children regularly, and another with school-age children aged 6-17 years, from three rural schools in Sekhukhune district, South Africa. The FGDs were guided by semi-structured interview questions. All sessions were recorded, transcribed verbatim, cleaned, coded, and analysed under ten domains, identified from the literature. Results A total of 477 statements and comments related to children’s vision were generated through the nine FGDs. Participants were nine experts working with children, and 49 children living with or without VI. Of the total number of statements, 60% (n = 287) were generated from FGDs with children, 63% (n = 299) were negative statements, and the remaining 19% (n = 92), and 18% (n = 86) were neutral and positive statements respectively. The most generated statements fell under the domains ‘Hobbies, Leisure and Sport’ 21% (n = 101), ‘Education’ 21% (n = 100), and ‘Psychological and Emotional’ 12.8% (n = 61). Conclusion This study offered comprehensive insights into the impact of VI on the daily activities of rural school-aged children and young people.